Nästa station - Cheong, En Qi (2015)
Set in a train station in a quiet city on the Swedish west coast, two strangers meet, decidedly or pushed by circumstance, and choose to spend an evening conversing with each other. It is revealed— as with all individuals, whether conscious or not— that both persons inherently struggle with their selves. Nästa Station delves into several issues, of cultural identity, the family as a site and source of the self, and the transient nature of certain encounters— at airports, bus stations, on trains, and wherever or whenever we travel.